2020
DOI: 10.3389/fimmu.2019.03116
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Associated Pemphigus Vulgaris in a Patient With Preceding Malignancy: Treatment With Rituximab as a Valuable Option

Abstract: Pemphigus is a chronic autoimmune blistering disorder, characterized by (muco-)cutaneous erosions due to autoantibodies against desmoglein 3 and/or 1. Pemphigus induction might be associated with drugs, malignancy or radiation therapy (RT); the latter being only rarely described. A rigorous literature review revealed around 30 cases of RT-associated pemphigus, which had been primarily treated with topical and/or systemic steroids, in some cases also dapsone or few other immunosuppressive agents were given. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In the literature, pemphigus occurrence in patients with underlying breast cancer has been reported as a particularly rare association, with most of the published cases occurring after radiation therapy. 4 Here, we describe a patient with a history of oral pemphigus vulgaris (PV) experiencing a severe disease flare predominantly affecting her right breast skin in the setting of an underlying ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, pemphigus occurrence in patients with underlying breast cancer has been reported as a particularly rare association, with most of the published cases occurring after radiation therapy. 4 Here, we describe a patient with a history of oral pemphigus vulgaris (PV) experiencing a severe disease flare predominantly affecting her right breast skin in the setting of an underlying ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In the case of our patient, a histopathological examination and direct immunofluorescence test were done, suggestive of drug-induced papulopustular dermatoses and pemphigus Vulgaris.Our patient showed a significant extent of severity of pemphigus (total activity score: 24) according to the PDAI scoring pattern as total activity score depends on the sum of total skin plus total scalp plus total mucosa (Table 1). 13 Our case was assessed as probable case using Naranjo adverse drug reaction probability scale which classify adverse drug reaction as definite (≥9), probable (5)(6)(7)(8), possible (1)(2)(3)(4) and doubtful (0) case. 14 PRIDE complex can be managed symptomatically.…”
Section: Discussionmentioning
confidence: 99%
“…2 About 5-11% of Pemphigus is related to malignancy. 4 Pemphigus Vulgaris is a rare mucocutaneous life-threatening disease usually characterized by painful blisters that initially starts from the mouth/oral cavity later involve other parts of the body and are not associated with itching and scar recovery. 1,2 Pemphigus Vulgaris has a higher incidence rate among the drug-induced Pemphigus, i.e., 0.1-0.5/100000 people/ year.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of these cases, we highlight a tendency toward the severity of these lesions with resistance to oral and general corticosteroid treatments in more than half of the cases (56%) as well as a tendency for the lesion progression in nonirradiated areas. Schauer et al [ 10 ] had indeed shown that for one-third of documented cases of radio-induced pemphigus, it is necessary to add an immunosuppressant to control the disease. In 3 cases, rituximab, an anti-CD20 monoclonal antibody, had been used for rapid and complete lesion remission.…”
Section: Discussionmentioning
confidence: 99%